Pengaruh Pelatihan Kerja, Motivasi dan Lingkungan Kerja terhadap Kinerja Karyawan: (Studi Kasus pada PT Anak Karya Cemerlang, Tangerang) - Devina Nurasiahn; Qodariah Qodariah (Jurnal Inovasi Manajemen, Kewirausahaan, Bisnis dan Digital, 2025)
This research was conducted to examine the impact of competence development and employee-related factors on work performance at PT Anak Karya Cemerlang. The sample of this study consisted of all employees of the company, while the selection of respondents was carried out using a probability sampling method with Slovin’s formula to ensure representativeness. Data were processed through multiple linear regression analysis, which allowed the researcher to assess both the partial and simultaneous effects of the independent variables on the dependent variable, namely employee performance. The findings reveal that professional training does not have a significant impact on employee performance, even though it was initially expected to enhance technical skills and work capabilities. This may be due to the fact that most employees already possessed sufficient work experience, making additional training less influential. In contrast, work motivation shows a significant effect on performance, as internal and external encouragement are capable of increasing enthusiasm, loyalty, and productivity. The work environment also demonstrates a significant influence, both in terms of physical comfort and the social climate within the workplace, where supportive conditions enable employees to perform optimally. Furthermore, the analysis indicates that training, motivation, and work environment simultaneously have a substantial impact on employee performance, with a coefficient of determination (R²) of 54.2%. This means that more than half of the variation in employee performance can be explained by these three variables, while the remaining 45.8% is influenced by other factors not examined in this study, such as leadership style, compensation, organizational culture, and individual characteristics. These findings emphasize the importance of prioritizing motivation and workplace conditions as key strategies for improving employee performance.